The Narrative of ‘Evidence Based’ Management: A Polemic - Morrell, Kevin (Journal of Management Studies, 2008)
abstract ‘Evidence based’ management is a popular contemporary account of the relationship between research and practice in management studies. This paper critically examines the implications of this account from the perspective of Formalism: a narratological approach to critique that focuses on how narratives are made compelling, and hence powerful. Compelling narratives deploy devices that establish (i) credibility and (ii) defamiliarization. Using this approach the paper identifies and examines different ideological strands in the nascent literature on evidence based management: pragmatism, progress, systematization, technique, accumulation. These are the means by which advocates of evidence based approaches construct a compelling story about the value of this approach. Prior criticism of the evidence based approach has centred on epistemological and technical issues. The aim here is to use an aesthetic mode of criticism to highlight political and moral implications. These are important given the relationship between claims to knowledge and the use of power; and the interaction between management research, and management as practice.